Adaptasi dan Validasi Skala Kecanduan Game Online untuk Siswa SMK - Prasetya, Agung (STKIP Muhammadiyah Pringsewu, 2019)
For most teenagers, the game is a fun entertainment activity. On the other hand, many conflicting views claim that modern online games can cause addictions which in turn leads to depression, isolation and dependence. The purpose of this research is to validate the online game addiction scale in SMK Negeri 2 Cilacap. Validity and reliability test results show that the scale consists of eight dimensions, namely online game usage, psychological dependence, compulsive usage, withdrawal, school or work related issues, sleep problems, family-related issues, and time-management issues. Subjects in this study amounted to 30 students of SMK. The results of statistical analysis show that the online game addiction scale is a valid and reliable instrument for measuring online game addiction that will be used school counselor to help measure the online game addicted to students in SMK Negeri 2 Cilacap. Keywords: Validity, Online Game Addiction.